Enforcement of labor market regulations: Heterogeneous compliance and adjustment across gender - Mariana Viollaz (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2016)
When compliance with labor market regulations is low, the enforcement of the labor law becomes a concept that is closer to the regulatory environment that firms and workers face. Firms are expected to react to variations in the enforcement level, and the response may differ for male and female workers. This paper explores microdata from Argentine household surveys to analyze: (i) how changes in the enforcement of labor regulations affect the level of compliance with the labor law among men and women, and (ii) how changes in the enforcement of the labor law generate adjustments of other labor outcomes, for men and women separately. Using information of the highly decentralized labor inspection system in Argentina, I construct an enforcement measure with variation at the province, sector, and time level (share of inspected firms). To deal with the potential endogeneity of this measure, I instrument using a measure of the arrival cost of labor inspectors to the firms. The main findings reveal different patterns of adjustment for men and women. When the degree of enforcement increases: the compliance with employment and social security regulations increases for men and decreases for women; the share of wage employees increases and the share of self-employed declines for men, with no changes for women; no changes are found in hourly wages and in the provision of non-mandated benefits. These results bring additional evidence about how the regulatory environment can impact on the decisions of firms and workers about participating in the informal sector. More importantly, they stress that both the written labor regulation and the degree of enforcement are essential parts in the provision of social and labor protection.
Keywords: 330